Iminodiacetic Acid (IDA) Cation-Exchange Nonwoven Membranes for Efficient Capture of Antibodies and Antibody Fragments - Jinxin Fan; Cristiana Boi; Solomon Mengistu Lemma; Joseph Lavoie; Ruben G. Carbonell (Membranes, 2021)
There is strong need to reduce the manufacturing costs and increase the downstream purification efficiency of high-value therapeutic monoclonal antibodies (mAbs). This paper explores the performance of a weak cation-exchange membrane based on the coupling of IDA to poly(butylene terephthalate) (PBT) nonwoven fabrics. Uniform and conformal layers of poly(glycidyl methacrylate) (GMA) were first grafted to the surface of the nonwovens. Then IDA was coupled to the polyGMA layers under optimized conditions, resulting in membranes with very high permeability and binding capacity. This resulted in IgG dynamic binding capacities at very short residence times (0.1–2.0 min) that are much higher than those achieved by the best cation-exchange resins. Similar results were obtained in the purification of a single-chain (scFv) antibody fragment. As is customary with membrane systems, the dynamic binding capacities did not change significantly over a wide range of residence times. Finally, the excellent separation efficiency and potential reusability of the membrane were confirmed by five consecutive cycles of mAb capture from its cell culture harvest. The present work provides significant evidence that this weak cation-exchange nonwoven fabric platform might be a suitable alternative to packed resin chromatography for low-cost, higher productivity manufacturing of therapeutic mAbs and antibody fragments.